Rain Harvester Prototype Integration for Drinking Water Using IoT And Mobile Apps - Muh. Fijar Sukma Kartika; Miftakhul Pebrianti Ningsih; Muhammad Aditya Darma Saputra; St. Shofiah Aghnani Alfi Laila Fq; Faris Febrian Hadianta; Mochammad Hannats Hanafi Ichsan (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
The drought that hit Indonesia caused 8 provinces in Indonesia to experience a crisis of clean water and drinking water. Meanwhile, the rainy season in Indonesia occurs for 6 months, starting from November to April. The peak of the rainy season in Indonesia occurs in January, with an average maximum rain intensity of around >700 mm. Based on the situation from the massive potential of rainwater in Indonesia, the possibility to produce clean water and drinking water to overcome drought problems in the dry season. The resulting drinking water must qualify according to its standards. Therefore, the water quality produced from this prototype must be observed. The purpose of this study is to determine the reliability of the filter on the rainwater harvester. The water filter materials used are zeolite natural stone, activated carbon stone, and filter cotton, and further filters are carried out through the Ultrafiltration membrane and electrolysis process. Then the water can be monitored for quality through the user's device. The external water quality of the rainwater harvester is tested with acidity or pH, Total Dissolve Solid or dissolved solids, and Turbidity or water clarity. The change in water quality is seen in TDS, from 50 ppm to 203 ppm. In addition, water quality is seen from the pH of 6.1 to 6.9 and for Turbidity of rainwater which is 0 NTU. Rainwater harvesters can convert rainwater into drinking water. However, in the future, there must be further research on the quality of water produced from rainwater harvesters.